MicroRNAs in cutaneous lichen planus. (1st December 2017) - El‐Rifaie, A. A.; Rashed, L. A.; Doss, R. W.; Osman, S. T.
Summary: Lichen planus (LP) is a chronic, inflammatory, papulosquamous, autoimmune disease. The pathogenesis of LP appears to be complex, with interactions between genetic, environmental and lifestyle factors. MicroRNAs (miRNAs) are short RNAs encoded in both protein coding and noncoding areas of the genome, and have been found to be involved in the pathogenesis of some inflammatory skin diseases. The aim of this study was to map the levels of miRNA (miR‐)‐203 and miR‐125b in cutaneous LP to evaluate their possible role in the pathogenesis of the disease. In total, 40 patients with classic cutaneous LP and 40 age‐ and sex‐ matched healthy controls (HCs) were enrolled in this study. Punch biopsies (4 mm) were taken from cutaneous LP lesions of patients and from normal skin of HCs. miRNA‐203 and miRNA‐125b mRNA expression was estimated by reverse transcription PCR. Our analysis revealed a significantly ( P < 0.001 for both) lower expression of both miR‐203 and miR‐125b mRNA in the LP than in the HC biopsies. No relationship was found between expression of miR‐203 or miR‐125b and either age, sex, presence of mucosal lesions or positivity for HCV antibodies. miR‐125b and miR‐203 could be involved in the pathogenesis of cutaneous LP.